2019
DOI: 10.4236/jbise.2019.121005
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Flu, SARS, MERS-CoV by CO<sub>2</sub> Emission and Maximal Sunspot Number

Abstract: The 1918 Spanish flu, 2002 severe acute respiratory syndrome (SARS), and 2012 Middle East respiratory syndrome coronavirus (MERS-CoV) were investigated to reveal their causes and routes of transmission. They have the common features such as 1) the induction by viruses (Spanish flu; avian influenza virus (AIV), SARS and MERS-CoV; coronavirus), 2) the outbreak during the maximal sunspot number, 3) the aeolian desert dust region (Spanish flu; Saharan, SARS; Asian, MERS-CoV; Arabian), and 4) similar incubation per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…A study by a colleague of the authors suggested that the twin peaks of the sunspot cycle in 2002 and 2012 were associated with the outbreak of severe acute respiratory syndrome (SARS) in China and Middle East respiratory syndrome (MERS) occurred in the Middle East (Qu and Wickramasinghe 2017). The sunspot number was considered an excellent factor to predict the scope and the extent of severe diseases for humans during the maximal sunspot number (Kim 2019). However, the sunspot number was not associated with the incidence of HFMD from our study.…”
Section: Discussioncontrasting
confidence: 71%
“…A study by a colleague of the authors suggested that the twin peaks of the sunspot cycle in 2002 and 2012 were associated with the outbreak of severe acute respiratory syndrome (SARS) in China and Middle East respiratory syndrome (MERS) occurred in the Middle East (Qu and Wickramasinghe 2017). The sunspot number was considered an excellent factor to predict the scope and the extent of severe diseases for humans during the maximal sunspot number (Kim 2019). However, the sunspot number was not associated with the incidence of HFMD from our study.…”
Section: Discussioncontrasting
confidence: 71%
“…Kim [5] proposed the minimal sunspot number strongly (R 2 = 0.9967) correlated with the avian influenza virus outbreaks. Kim [7] also showed that there was a close relationship (R 2 = 0.8539) between MERS-CoV in Eastern Mediterrane region and maximal sunspot number from 2012 to 2018.…”
Section: Introductionmentioning
confidence: 85%
“…Kim [6] also showed that there was a close relationship (R 2 = 0.8539) between MERS-CoV in Eastern Mediterrane region and maximal sunspot number from 2012 to 2018.…”
Section: Introductionmentioning
confidence: 85%
“…When CO 2 is increased, ozone (O 3 ) layers in the Poles become thinner so that UV radiation [5] upon the Earth is increased. Increased solar radiation during maximal sunspot number [6] and enhanced CO 2 emission may induce El Niño events through warm SST and strong volcanic eruptions at seamounts in Antarctica, South America, and GHS.…”
Section: El Niño Index and La Niña Index With Sunspot Numbermentioning
confidence: 99%